Mathematics of computation. Volume 69, Number 230, 2000 - American Mathematical Society (American Mathematical Society, 2009)
Contents of Volume 69, Number 230 View front matter and back matter from the print issue of this journal View front and back matter from the print issue All articles in this issue are available free of charge